Black Trauma in Toni Morrison's Beloved - Shakti Brammaditto Widya Fachrezzy; Thohiriyah (Universitas Islam Negeri Palopo, 2025)
Toni Morrison’s Beloved offers a powerful literary response to the enduring wounds of slavery and racial violence. This study aims to analyze how the novel illustrates Black trauma as a shared, inherited, and historically grounded condition. Drawing on Frantz Fanon’s theory of colonial trauma, the analysis focuses on psychological fragmentation, social alienation, and embodied memory to reveal the lingering effects of oppression across time and generations. Using a qualitative approach, the study examines Morrison’s narrative methods and character portrayals. Ultimately, the novel frames healing as a nonlinear process rooted in reconnection, acknowledgment, and resistance.